Use of Technology in Active Learning: Increasing Student Interaction and Engagement - Wibowo, Guntur Arie; Karim, Aim Abdul; Hasan, Said Hamid; Ruhimat, Mamat (Al-Hijr: Journal of Adulearn World, 2023)
In today's digital age, the world is faced with rapid technological advances. It is undeniable that education today must be able to keep up with these advances. This technology can be utilized in various forms of media such as WA groups, classrooms, zoom and so on for distance learning facilities. However, many schools have not fully utilized technology. Moreover, currently there are many cases of students being less active, less interacting and involved during distance learning. So this research emerges to answer this problem with a focus on the utilization of technology in an effort to increase student interaction and involvement in active learning. The purpose of this research is to investigate the impact of technology utilization in active learning. Then to find out the extent to which technology can encourage student interaction. Through technology, it is also possible to measure the level of student engagement in distance learning. The research method used is quantitative method. Data was obtained through distributing questionnaires to students online utilizing google form. The results obtained from respondents during the distribution of questionnaires were then processed into an application called SPSS with the oneway anova test. After processing the data, the researcher then presents the data in the form of a table containing the response rate of the respondents. The results of this study show that technology has a positive impact. Technology brings active learning. Learning is more fun, interesting and not boring. Then technology is able to increase interaction between students and students, student interaction with learning so that learning is effective. The conclusion of the research is that technology is an important tool used in the fields of life today such as government, economy, social, media, including education. The technology is very much needed in the world of education. The integration of technology wisely in the context of active learning is able to increase student interaction and involvement so as to facilitate the learning process so that educational goals are achieved and the quality of education increases.